2022
DOI: 10.1007/s00384-022-04105-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of extracolonic second primary cancers following a primary colorectal cancer: a systematic review and meta-analysis

Abstract: Purpose The purpose of the study is to assess the global risk of extracolonic secondary primary cancers (SPCs) in patients with colorectal cancer (CRC). Methods Studies of SPC in patients with CRC were included if they reported the standardised incidence ratio (SIR) for extracolonic SPCs in patients with CRC compared with the general population. Pooled summary estimates were calculated using a random-effects model. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…We found higher kidney and bladder cancer cases numbers than expected. This is consistent with Robertson’s review, published in early 2022, which showed a pooled SIR equal to 1.19 (95% CI 1.06–1.33; p = 0.003) for bladder and to 1.50 (95% CI = 1.19–1.89; p = 0.0007) for kidney cancer [ 29 ]. Our results are close to these values, and the limited significance probably reflect the small sample size we observed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found higher kidney and bladder cancer cases numbers than expected. This is consistent with Robertson’s review, published in early 2022, which showed a pooled SIR equal to 1.19 (95% CI 1.06–1.33; p = 0.003) for bladder and to 1.50 (95% CI = 1.19–1.89; p = 0.0007) for kidney cancer [ 29 ]. Our results are close to these values, and the limited significance probably reflect the small sample size we observed.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other studies. Robertson and coworkers assessed a pooled SIR of 1.22 for stomach cancer (95% CI = 1.07–1.39; p = 0.003) in their review [ 29 ]. We found a higher magnitude of this association, despite the small sample size prevent us from a full comparison with Robertson’s data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the incidence of SPC among CRC survivors using large epidemiological cancer registry data covering over a third of the German adult population. Similar to previous reports from other national cancer registries, we found an elevated risk of a second cancer after CRC, particularly in the digestive system, respiratory tract, urinary system and prostate in males, female reproductive organs 15,[26][27][28][29] as well as second primary CRC. 17,27 This risk is pronounced in survivors <65 years of age, as previously observed.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the general population, individuals diagnosed with colorectal cancer face a notably higher likelihood of developing extracolonic secondary primary cancers. Among these secondary cancers, a considerable portion is attributed to obesity-related cancers like endometrial cancer (EC) [9,10] . Aside from breast, ovarian, cervical, and colorectal cancers, EC is the second most prevalent primary cancer [11][12][13][14][15] , and Previous research has indicated that chemotherapy for breast cancer and radiotherapy for cervical cancer elevate the likelihood of SEC [16,17] .…”
Section: Introductionmentioning
confidence: 99%